Factors that contributed to default in credit card repayment / Normala Othman - Othman, Normala (Faculty of Business and Management, 2011)
Cashless trend has driven an increasing number of people that use credit card to facilitate their transaction. A credit card is a system of payment named after the small plastic card issued to users of the system. Like another credit, credit card faced a default risk. This study investigates the factors that contributed to default in credit card repayment. It consists of three factors there are income level, interest rate and consumer’s attitudes toward default in credit card repayment. The research findings show that the most factors that contributed to default in credit card repayment. This research where been used the convenience sampling to get the data that are required. The research population is the employees at Perbadanan Kemajuan Negeri Melaka (The State Economic Development Corporation) who are credit cardholders. About 50 respondents were getting from this research to help for accomplish this research by answering the questionnaire had been distributed to them. All the data collected through the questionnaire were analyzed systematically by Statistical Package for Social Science (SPSS 11.5). The conclusion of this study was outcome from the data analysis and findings. Through the research, it shows based on Reliability, Frequency, Correlation Coefficient, and Multiple Regression where a clear finding and results are observed. The finding shows that consumer attitudes are the most factors that contributed to default in credit card repayment. The researcher also finds that customer income and interest rate have positive impact on credit card default.